Digital poverty in Sabah: Socioeconomic factors shaping digital accessibility during the postcovid-19 era - Norhuda Salleh; Rachel Mina William; Romlah Ramli; Noor Syakirah Zakaria; Fiffy Hanisdah Saikim; Asmiaty Amat; NorIna Kanyo; Dr. Dg Marshitah Pg Baharuddin; Ahmad Murad Mohd Merican (Human Resource Management Academic Research Society (HRMARS), 2023)
As Malaysia strives to progress within the framework of Industrial Revolution 4.0 (IR 4.0), there is a burgeoning concern for digital poverty. The rapid evolution of technology has, regrettably, exacerbated the divide between the privileged and the underprivileged, further perpetuating an unbreakable cycle of digital poverty. Consequently, this study delves into the impact of socioeconomic factors on digital technology accessibility in Sabah's community during the post-Covid-19 era. A quantitative survey, employing Google Forms, engaged 724 respondents from various locations across Sabah. The findings underscore a stark digital divide in Sabah, particularly affecting households in rural areas and those with limited educational attainment. To bridge this gap, endeavors should prioritize enhancing digital infrastructure access in rural locales and fostering digital literacy and education among underserved demographics.